Treatment outcomes of pulpotomy in primary teeth with irreversible pulpitis: a systematic review and meta-analysis - Lin, Galvin Sim Siang; Chin, Yu Jie; Choong, Rob Son; Syed Saadun Tarek Wafa, Sharifah Wade’ah Wafa; Dziaruddin, Nabihah; Baharin, Fadzlinda; Ismail, Ahmad Faisal (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Aim: This systematic review and meta-analysis aimed to evaluate the success rates of pulpotomy treatment for irreversible pulpitis in primary teeth. Methods: This study was registered and conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. Relevant studies published between January 1980 and April 2023 were identified across eight online databases and two paediatric dentistry textbooks. Study selection, data extraction, and quality assessment were conducted by multiple investigators independently. Data analysis involved single-arm and two-arm meta-analyses, leave-one-out sensitivity analysis, meta-regression, and assessment of publication bias. The risks of bias were evaluated using the Cochrane Collaboration’s assessment tools. The levels of evidence were determined using the Oxford Centre for Evidence-Based Medicine (OCEBM) tool. Results: Five primary studies were included. The weighted mean overall success rates at 6-month and 12-month follow-ups were 97.2% and 94.4%, respectively. Two-arm meta-analysis revealed no significant difference (p > 0.05) between the use of mineral trioxide aggregate (MTA) and non-MTA bioceramic-based materials as pulpotomy medicaments. The sample size of each study did not affect the degree of data heterogeneity. Egger’s test revealed no significant publication bias. Conclusions: Pulpotomy may be regarded as an alternative modality for treating primary teeth with irreversible pulpitis. Nevertheless, future well-designed trials and extended follow-up periods are warranted.